Genetic insights into the gut microbiota, herpes zoster, and postherpetic neuralgia: a bidirectional two-sample Mendelian randomization study - Deng, Zhimin; Liu, Yali; Wang, Haiying; Luo, Tianyuan (Frontiers in Genetics, 2024)
Background: An increasing amount of evidence suggests that gastrointestinal diseases are a risk factor for herpes zoster (HZ) and postherpetic neuralgia (PHN). Among them, the gut microbiota may play a crucial role in this process. Therefore, this study aims to explore the potential causal association between gut microbiota and HZ and PHN.Methods: Bidirectional two-sample Mendelian randomization (MR) analysis was used to detect the causal effect between HZ, PHN and gut microbiota. Gut microbiota data were derived from MiBioGen consortium. While, HZ and PHN data obtained from the FinnGen database. We selected single nucleotide polymorphisms (SNPs) as instrumental variables with a threshold of P < 1 × 10⁻⁵ for association with gut microbiota in forward MR analysis and P < 5 × 10 ⁻8 for association with HZ or PHN in reverse MR analysis and then removed SNPs in linkage disequilibrium (r² < 0.001) within a distance of 10,000 kb for both gut microbiota and HZ, PHN . These SNPs were utilized to assess the causal effect between exposures and outcomes using inverse variance weighting (IVW), MR-Egger, weighted mean, and weighted median test.The class Deltaproteobacteria, order Desulfovibrionales, family Desulfovibrionaceae , and genus Coprococcus 2 were found to reduce the risk of HZ, while the phylum Cyanobacteria , genus Eubacterium rectale group appeared to increase it. The class Coriobacteriia , order Coriobacteriales , family Coriobacteriaceae, genus Lachnospiraceae NK4A136, genus Ruminococcaceae UCG011 were found to reduce the risk of PHN, while the genus Candidatus Soleaferrea, genus Eubacterium rectale group , genus Methanobrevibacter appeared to increase it. Moreover, the onset of HZ was found to increase the level of genus Eubacterium rectale group. These findings remained robust and unaffected by heterogeneity or horizontal pleiotropy among SNPs in both forward and reverse MR analysis.This MR study has provided evidence supporting a potential causal relationship between gut microbiota and HZ and PHN. Moreover, we found that the causal effect between gut microbiota and HZ is bidirectional. Further studies are required to clarify the biological mechanisms linking gut microbiota and these conditions.